Angioimmunoblastic T-Cell Lymphoma: A Questionable Association with Follicular Dendritic Cell Sarcoma - Daniel Benharroch; Miriam Zekzer; Karen Nalbandyan (Case Reports in Hematology)
An elderly woman presented with generalized lymphadenopathy, several systemic symptoms, and splenomegaly. An inguinal lymph node excision revealed a compound picture. One aspect of the lymph node morphology, including cells with follicular T-helper cell phenotype, was most consistent with angioimmunoblastic T-cell lymphoma. The other component, revealing spindle cells forming whorls with immunostaining for CD21, CD23, and fascin, might be an integral part of this T-cell lymphoma. However, due to the often massive involvement of the nodal tissue by these follicular dendritic cells, these areas were questionably suggestive of involvement by follicular dendritic cell sarcoma. We raise herein the issue of the borderline area between advanced follicular dendritic cell expansion in angioimmunoblastic T-cell lymphoma and a massive follicular dendritic cell proliferation consistent with follicular dendritic cells sarcoma, in the absence of a genomic analysis.